Nanocomplex hyaluronic acid/ganciclovir@ZIF-8 for ganciclovir efficient delivery and targeted anti-KSHV treatment - Fangling Li; Chengjing Liu; Wenyi Gu; Qianhe Xu; Dongmei Li; Dongdong Cao; Zhiyong Liu (Cancer Nanotechnology)
Abstract Kaposi's sarcoma-associated herpesvirus (KSHV) infection can cause a variety of tumors and is one of the leading causes of death in acquired immune deficiency syndrome (AIDS) patients. As a small molecule antiviral drug, ganciclovir (GCV) can be used for anti-KSHV treatment. However, GCV has non-specific action and toxic side effects in vivo, and how to make it safer and more effective against KSHV is still a great challenge. By encapsulating GCV into metal–organic skeleton material zeolitic imidazolate framework-8 (ZIF-8) and further modification of hyaluronic acid (HA), the nanomedical delivery system of GCV (HA/GCV@ZIF-8) has been developed for efficient GCV delivery and targeted anti-KSHV treatment. The modification of HA leads to the targeted binding of the nanocomplex with the overexpressed CD44 receptors in tumor cell membranes, resulting in the increased accumulation and cellular uptake of GCV. Exploiting the decomposition property of ZIF-8 under acidic conditions, the nanocomplex exhibits pH-responsive drug release in slightly acidic tumor environment. In addition, HA/GCV@ZIF-8 not only suppresses expression of KSHV pathogenic genes with less drug dose, but also inhibits the ability of cell proliferation and migration. In vivo anti-tumor results showed that HA/GCV@ZIF-8 accumulated in tumor cells and effectively inhibited tumor growth. The results open a gate for the targeted anti-KSHV treatment. Graphical Abstract